2012
DOI: 10.3892/ijmm.2012.1094
|View full text |Cite
|
Sign up to set email alerts
|

Tacrolimus (FK506) suppresses TNF-α-induced CCL2 (MCP-1) and CXCL10 (IP-10) expression via the inhibition of p38 MAP kinase activation in human colonic myofibroblasts

Abstract: Abstract. In order to investigate the molecular mechanisms underlying the immunosuppressive effects of tacrolimus (FK506) on intestinal inflammation, we examined whether FK506 effects cytokine/chemokine secretion in human colonic myofibroblasts. Human colonic myofibroblasts were isolated from normal human colonic tissue. The mRNA and protein expression for human CCL2 and CXCL10 were analyzed by real-time PCR and ELISA, respectively. p38 MAP kinase activation was evaluated by western blotting. Tacrolimus (1 µM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 49 publications
2
21
0
Order By: Relevance
“…The fact that Ficz-mediated abrogation of p38 and ERK1/2 activation was accompanied by a 60% reduction of cytokine-driven collagen synthesis advocates a major role for MAP kinases in the control of collagen production in CD fibroblasts. This is in line with other reports showing the involvement of MAP kinases in the chemokine and profibrotic factor response of intestinal fibroblasts to inflammatory cytokines [35]. The lack of effect of AhR activation or inhibition on Smad2/3 and NF-κB activation in response to TGF-β or TNF-α is noteworthy as these findings indicate that AhR activation does not induce a state of global unresponsiveness in intestinal fibroblasts, perhaps explaining why proliferation and survival of these cells were not affected by Ficz or CH223191.…”
Section: Discussionsupporting
confidence: 93%
“…The fact that Ficz-mediated abrogation of p38 and ERK1/2 activation was accompanied by a 60% reduction of cytokine-driven collagen synthesis advocates a major role for MAP kinases in the control of collagen production in CD fibroblasts. This is in line with other reports showing the involvement of MAP kinases in the chemokine and profibrotic factor response of intestinal fibroblasts to inflammatory cytokines [35]. The lack of effect of AhR activation or inhibition on Smad2/3 and NF-κB activation in response to TGF-β or TNF-α is noteworthy as these findings indicate that AhR activation does not induce a state of global unresponsiveness in intestinal fibroblasts, perhaps explaining why proliferation and survival of these cells were not affected by Ficz or CH223191.…”
Section: Discussionsupporting
confidence: 93%
“…miR-34a regulates its target gene expression by binding to the 3'-UTR of its target mRNA [34]. Aomatsu et al reported that CXCL10 expression in colonic myofibroblasts is suppressed by tacrolimus and that overexpression of miR-34a represses its target gene CD44 in osteosarcoma cells [35, 36]. The down-regulation of CXCL10 might be caused by c-Fos, a prominent member of the AP-1 family, when mediated by TNF-related apoptosis-inducing ligand [37].…”
Section: Discussionmentioning
confidence: 99%
“…Mouse serum was analyzed for the presence of circulating human inflammatory cytokines including: interleukin-6 (IL-6) 16 , interferon γ (IFNγ) 17 , interleukin-5 (IL-5) 18 , monocyte chemotactic protein-1 (MCP-1) 19 , macrophage inflammatory protein (MIP)-1β 20 , interferon inducible protein-10 (IP-10) 21 and tumor necrosis factor α (TNFα) 22 to determine whether the administration of Treg had any impact on the in situ production of these factors. In all cases, levels of circulating inflammatory cytokines were decreased if CB Treg were introduced before administration of PBMC.…”
Section: Resultsmentioning
confidence: 99%